Taboo language research in the new millennium: A literature review - Crespo-Fernández, Eliecer (Complutense Journal of English Studies, 2025)
Taboo and taboo naming are not single, unified phenomena that can be addressed from a single perspective. Indeed, in the last twenty-five years, linguistic research on taboo avoidance and taboo breaking, that is, on euphemism and dysphemism, has spanned across different, yet interconnected, linguistic fields, including cognitive semantics, discourse studies, pragmatics and sociolinguistics, among others. In this regard, the goal of this paper is to offer an overview of the state of work in taboo-related research in the twenty-first century (2000-2024) in the Anglophone academic context and, by doing so, make the existing work accessible to a wide academic community. This study provides insights into the academic disciplines involved in taboo language research, main publication formats, most cited publications and relevant journals in the field. The literature review shows that discourse analysis, sociolinguistics and pragmatics rank the most relevant research disciplines, followed, at a distance, by cognitive semantics, psycholinguistics and translation studies. Accordingly, the academic journals publishing work on taboo-related language range from those that are general in scope to others devoted to specific research areas or subjects, which shows the interdisciplinary nature of taboo language research in the new millennium.